Kurang Tidur dan Regulasi Nafsu Makan: Tinjauan Mekanisme Hormonal dan Metabolik - Rossy Triana; Desak Ketut Indrasari Utami (PT Dexa Medica, 2026)
Sleep deprivation has become an increasingly prevalent global health issue in the modern era. This condition not only affects cognitive function and quality of life but is also closely associated with the regulation of appetite and metabolic processes. Numerous studies have demonstrated that sleep insufficiency triggers hormonal changes, including increased ghrelin level, decreased leptin level, and alterations in other hormones involved in hunger and satiety regulation. These physiological changes promote increased energy intake, particularly from calorie-dense foods, while weakening cognitivecontrol over eating impulses. Moreover, sleep deprivation has been shown to reduce insulin sensitivity, increase insulin resistance, and disrupt glucose homeostasis, thereby contributing to the risk of obesity, type 2 diabetes, and metabolicsyndrome. Therefore, adequate and good-quality sleep plays a crucial role in maintaining metabolic balance and preventing long-term health complications.